Pedagogical effectiveness in the school organizational culture and the professional learning community - Mendoza Velazco, Derling José (2021)
The objective of this study was to analyze teacher effectiveness in the organizational culture of schools and the professional learning community. This was a quantitative research, with a simple random sample of 359 elementary teachers at the initial, basic, and general unified level in the cities of Cuenca and Azogues, Ecuador. Four Likert-type questionnaires of five answer options were applied as instruments, with the t, F, and Scheffé test analysis method. Using correlation and multiple regression analysis, results indicated that teachers respond to school organization according to their personal characteristics. The school organizational culture is gradually being transformed into a positive and ideal culture. The professional learning community had a positive effect on teachers' effectiveness. In conclusion, the organizational culture of the school and the professional learning community should go beyond the interactive dimension and move towards the integration dimension to improve the school in order to obtain greater pedagogical effectiveness.